HETEROSIS OF SOME TROPICAL MAIZE GENOTYPES DERIVED FROM TWO DIFFERENT MAIZE BREEDING ERAS - Sunday, Ige AYODELE (Bangladesh Journal of Plant Breeding and Genetics, 2017)
Heterosis for maize grain yield was studied to identify cross combinations that may be useful sources for inbred line extraction, recurrent selection and, to estimate changes in the maize grain yield heterosis across two breeding eras in the tropics. Field studies were conducted at the International Institute of Tropical Agriculture (IITA), Ibadan during the cropping seasons of 2010, 2011 and 2012, with 10 open pollinated maize varieties (OPVs) derived two breeding eras (1 and 2). The ten OPVs and the crosses generated from them were evaluated under stem borer infested and non-infested, high-N versus low-N and natural conditions. Mid and High-heterosis (MPH & HPH) were estimated from grain yield data from the tested environments. MPH & HPH under natural, optimum N-Fertilizer application, and borer infested environments were 37.20 and 25.38%, 19.85 and 12.3%, 30.98 and 18.94% respectively. Cross combination DMR-LSR-W (Era 1) x TZSR-Y-I (Era 1) expressed the highest magnitude of (MPH & HPH) (97.70 and 87.15%) for grain yield across the tested environments except low-N. It suggest the suitability of the hybrid for cultivation only in environments with high productivity index. Hybrid ACR99TZLCOMP4-DMRSR (Era 1) x BR9928DMRSR (Era 2) had highest HPH under low-N environments. Suggesting this combination as a good source of genes for the development of low nitrogen tolerance maize varieties in the tropics. Cross combinations that expressed better (HPH) under borer infestation are good gene pools for the development of stem borer tolerance maize varieties in stem borer endemic zone. These crosses hold promise as future candidates for commercial exploitation of heterosis or for the extraction of inbred lines in the tropics. Better (HPH) were derived from the crosses between Era 1 and & 2, indicates the older and newer maize varieties complement each other for (HPH) across environments.